A new species of the bromeligenous Scinax perpusillus group (Anura; Hylidae) from Serra do Brigadeiro, State of Minas Gerais, Southeastern Brazil - Lacerda, João Victor A.; Peixoto, Oswaldo Luiz; Feio, Renato N. (Zootaxa, 2012)
A new species of the bromeligenous Scinax perpusillus group is described from Serra do Brigadeiro, state of Minas Gerais,southeastern Brazil (20º43’13.5´´S; 42º28’48.7´´W). Scinax cosenzai sp. nov. is diagnosed by a combination of traits:moderate-size within the group (17.29–20.97 mm in males and 22.65–24.02 mm in females); head longer than wide; snoutprotruding in lateral view and slightly acuminated in dorsal view; prominent medial process between the nostrils; few tu-bercles scattered throughout the dorsal surface, including the head; ventral skin granulated, more intensively near the clo-acal region; dorsum different tones of gray with dark bands; transversal dark bars along limbs; gular region with irregulardark pigmentation; in life, hidden portion of the thigh and tibia region with some irregular bright yellow colored patches;and a distinct advertisement call with 2–14 notes/call, call duration 177.62–2066.75 ms, 1–33 pulses/note and dominant frequency of 3375.91–4571.21 Hz. Additionally, notes on natural history are provided.